Eliciting the institutional myth: exploring the ethos of 'the university' in Germany and England. Issue 2 (3rd April 2018) - Budd, Richard
ABSTRACT: This paper is situated in relation to a critical mass of largely censorious commentary around global policy trends purportedly undermining, or even realigning, universities' 'traditional' ethos, but where the student perspective on this appears to have been largely ignored. Drawing on interviews with German and English undergraduates, it applies the neo-institutional theory of organizational fields supported by regulative, cognitive, and normative pillars (Scott 1995. Institutions and Organi zations . Thousand Oaks: Sage). The latter pillar, representing a sector's values, methods, and goals, is of particular interest here, and it will be argued that this and an ethos may correspond. The findings show that a sense of the participants' understanding of a university ethos/normative pillar could be discerned, with significant convergence between the two groups. However at the same time there was also divergence both within and between them, and this raises a number of novel empirical and theoretical questions.